Analysis of a Model Arising from Invasion by Precursor and Differentiated Cells - Xiaojie Hou (International Journal of Differential Equations, 2013)
We study the wave solutions for a degenerated reaction diffusion system arising from the invasion of cells. We show that there exists a family of waves for the wave speed larger than or equal a certain number and below which there are no monotonic wave solutions. We also investigate the monotonicity, uniqueness, and asymptotics of the waves.